2010
DOI: 10.1590/s0103-84782010005000166
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility and fecal characteristics of dogs fed with Bacillus subtilis in diet

Abstract: Considering the benefice demonstrated by the modulating action of probiotics on the host intestinal microbiota, this study aimed to evaluate diet digestibility and fecal characteristics of dogs fed with diets supplemented with Bacillus subtilis (C-3102). Twelve young Beagle dogs were distributed in a completely randomized experimental design consisting of two treatments: diet with no addition or with the addition of 0.01% Bacillus subtilis (C-3102). Dogs passed through 25 days of adaptation to the diets, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 6 publications
(7 reference statements)
5
21
0
Order By: Relevance
“…However, elevated lactic acid in feces of the fermented vs. non-fermented snack did not affect fecal pH. Decreased ammonia content and increased lactic acid in feces induced by dietary fermented snack may be in part secondary to balanced gut microbiota, i.e., LAB which could then inhibit pathogenic bacteria [21].…”
Section: Effect Of Feeding Of the Fermented And Non-fermented Snacks mentioning
confidence: 88%
“…However, elevated lactic acid in feces of the fermented vs. non-fermented snack did not affect fecal pH. Decreased ammonia content and increased lactic acid in feces induced by dietary fermented snack may be in part secondary to balanced gut microbiota, i.e., LAB which could then inhibit pathogenic bacteria [21].…”
Section: Effect Of Feeding Of the Fermented And Non-fermented Snacks mentioning
confidence: 88%
“…; Félix et al . ). However, mere survival might be not the most important feature of a probiotic, and they all need to be tested for their benefit in clinical situations.…”
Section: The Effect Of Probiotics On Selected Parameters In Healthy Dogsmentioning
confidence: 97%
“…Only one study found that Bacillus subtilis C‐3102 can improve faecal texture and odour in dogs due to a decreased content of faecal ammonia (Félix et al . ). Once again, the clinical relevance of this finding and the justification of calling bacilli ‘probiotics’ in this situation is highly questionable and the usage of Bacilli as probiotics cannot be recommended.…”
Section: The Effect Of Probiotics On Selected Parameters In Healthy Dogsmentioning
confidence: 97%
“…DFM has been defined by the US Food and Drug Administration as the feed product containing the source of naturally-existing live microbes, like some bacteria of the Bacillus genus. When supplemented in the diet, these microorganisms may favour non-pathogenic bacteria [5,6].…”
Section: Introductionmentioning
confidence: 99%